2014
DOI: 10.3390/polym6082232
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Graphene Nanoplatelets and Reduced Graphene Oxide on Poly(lactic acid) and Plasticized Poly(lactic acid): A Comparative Study

Abstract: Abstract:The superlative mechanical properties of graphene-based materials make them the ideal filler materials for polymer composites reinforcement. Two types of graphene-based materials, graphene nanoplatelets (xGnP) and reduced graphene oxide (rGO), were used as nanofiller in poly(lactic acid) (PLA) polymer matrix, as well as plasticized PLA. The addition of rGO into PLA or plasticized PLA substantially enhanced the tensile strength without deteriorating elasticity, compared to xGnP nanocomposites. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
34
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(45 citation statements)
references
References 31 publications
9
34
0
2
Order By: Relevance
“…The peaks at 1450-1375 cm -1 are due to the symmetric deformation of C-H stretching in the CH3, while the peaks at 1100-950 cm -1 are attributed to C-O stretching. Similar peaks were reported for PLA films in the literature(Chieng et al, 2014;A. González & Alvarez Igarzabal, 2013;Haafiz et al, 2013).…”
supporting
confidence: 87%
“…The peaks at 1450-1375 cm -1 are due to the symmetric deformation of C-H stretching in the CH3, while the peaks at 1100-950 cm -1 are attributed to C-O stretching. Similar peaks were reported for PLA films in the literature(Chieng et al, 2014;A. González & Alvarez Igarzabal, 2013;Haafiz et al, 2013).…”
supporting
confidence: 87%
“…The choice of the preparation method of graphene‐based nanocomposites depends on the polarity, molecular weight, hydrophobicity, surface functionalization of graphene, and reactive groups of the polymer, graphene and solvent . As it is evident from the works referred in the last section, the 3 most popular methods of manufacturing graphene derivatives‐polymer composites are solution mixing, melt blending, and in situ polymerization . Other methods have been occasionally reported for producing graphene‐based composites such as the layer‐by‐layer technique …”
Section: Preparation Methods Of Graphene Polymer Nanocompositesmentioning
confidence: 99%
“…The effect of incorporation of xGnP in a PLA‐PEG matrix was also evaluated by Chieng et al PLA was plasticized by PEG, then xGnP was incorporated into the PLA/PEG matrix, by melt blending. Compared with PLA/PEG blends, the resultant nanocomposites exhibited enhanced thermal stability and a significant improvement in the mechanical properties, similar to the work of Pinto et al The composites demonstrated an increase of up to 32.7 , 69.5, and 21.9 wt% in the tensile strength, tensile modulus, and elongation at break, respectively, only with the addition of 0.3 wt.% of xGnP …”
Section: Graphene‐based Nanocompositesmentioning
confidence: 99%
“…For the same scaffold type, the PLLA/C-HAP scaffold possessed a higher tensile strength and modulus than the PLLA/HAP scaffolds, and this was mainly due to the better dispersion states and effective interfacial bonding. Apart from improving the biological properties, the ceramic phase was added in an attempt to also improve the mechanical properties of scaffold [29][30][31]. However, aggregates would hinder the reinforcing effects contributing to uneven stress transfer [32].…”
Section: Mechanical Propertiesmentioning
confidence: 99%